Methodology for Developing Students’ Ecological Competence through an Integrative Pedagogical Model in Biology and Microbiology Education (Eurasian Research Bulletin, 2025)
This article presents a didactic model aimed at enhancing students’ ecological competence through the teaching of biology and microbiology within the undergraduate program “Ecology and Environmental Protection.” The model is based on interdisciplinary integration, developmental education, and a value-oriented approach. It emphasizes meaning-making through student-centered learning principles such as personal experience, reflection, and collaborative learning. The proposed methodology is suitable for technical higher education institutions and contributes to the formation of ecological awareness and sustainable thinking